DESI 2024: a possible indication of the end of the cosmological constant? - Velten, Hermano; Marttens, Rodrigo von (Cadernos de Astronomia, 2024)
Discussion on the release of the first results from the Dark Energy Spectroscopic Instrument (DESI), based on the measurement of the impressions left by baryon acoustic oscillations in the distribution of galaxies and quasars. These results suggest, for the first time in academic literature, a temporal variation in the equation of state of the dark energy component of the universe. The DESI project is briefly explained, its operation and how modern cosmology can be impacted if this result is effectively consolidated by future observations.